2020
DOI: 10.3390/molecules25030635
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Intra and Intermolecular Triel Bonds. Complexes between Naphthalene Derivatives and Neutral or Anionic Lewis Bases

Abstract: : A TrF2 group (Tr = B, Al, Ga, In, Tl) is placed on one of the α positions of naphthalene, and its ability to engage in a triel bond (TrB) with a weak (NCH) and strong (NC−) nucleophile is assessed by ab initio calculations. As a competitor, an NH2 group is placed on the neighboring Cα, from which point it forms an intramolecular TrB with the TrF2 group. The latter internal TrB reduces the intensity of the π-hole on the Tr atom, decreasing its ability to engage in a second external TrB. The intermolecular TrB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 108 publications
(113 reference statements)
0
20
0
Order By: Relevance
“…There are similarities between the triel [21] and tetrel atoms with respect to their behavior when confronted with the possibility of both internal and external noncovalent bonds. In both cases, there is an anticooperative effect in that the two bonds tend to weaken one another.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are similarities between the triel [21] and tetrel atoms with respect to their behavior when confronted with the possibility of both internal and external noncovalent bonds. In both cases, there is an anticooperative effect in that the two bonds tend to weaken one another.…”
Section: Discussionmentioning
confidence: 99%
“…Some recent work by this group has considered the competition between inter and intramolecular bonds in the context of the related triel bond [21] . It was found that theTrF 2 (Tr=B, Al, Ga, In, Tl) group connected to the C α atom of a naphthalene unit formed a noncovalent bond with an approaching NCH nucleophile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Thus a large number of theoretical and experimental studies of triel bonds have appeared in recent years. [20][21][22][23][24] These studies have revealed a number of unusual characteristics of triel bonds. Although a Tr atom with a deeper π-hole will generally form a stronger triel bond, BF 3 participates in a weaker triel bond than does BH 3 in spite of the deeper π-hole of the former.…”
Section: Introductionmentioning
confidence: 99%
“…Our quest to shed more light onto self-assembly of molecules, and reveal how atoms and molecules form larger structures at nanoscale, requires detailed description of intra- and intermolecular forces. Especially interesting cases are those in which these types of forces compete, and the final outcome is a result of a delicate balance [ 9 , 10 , 11 , 12 , 13 ]. Herein, we present a study of anthraquinone derivatives in which diverse types of intermolecular forces are affected by intramolecular hydrogen bonding and substituent effects.…”
Section: Introductionmentioning
confidence: 99%